Shinrin-yoku/ Forest bathing: a natural way to promote health, prevention and cure diseases. The heritage of Master Peter Dunov in Forest Medicinе (Research Announcements "Heritage BG", 2025)
Shinrin-yoku or Forest Bathing is a traditional Japanese practice that involves immersing oneself in nature and mindfully engaging all five senses. This practice was introduced by the Japanese government in the 1980s to help urban residents cope with work-related stress. There are currently 60 studies available in the medical database PubMed that are related to Shinrin-yoku. Publications can be divided into the following main areas: health promotion, disease prevention, and treatment. The effects of forest bathing on health include improved cardiac and vascular function, blood pressure-lowering effects, decreased blood glucose levels in diabetic patients, pain reduction, enhanced mental health, benefits for neurological rehabilitation, support for individuals with intellectual disabilities, and potential benefits for COVID-19 recovery. The research draws a parallel with the heritage of Teacher Dunov in forest therapy. References:Ancheva 2007: Ancheva, Daniela. Specializaciq za prepodavateli po Panevritmia: usloviq, poleznost, vyzmojnosti: Treta nauchna konferencia po Panevritmia. Institut za izsledvane i prilagane na Panevritmiyata, ISBN-10: 954-90922-5-9. ISBN-13: 978-954-90922-5-7. Sofia, 2007, 100-108.Chervenkova 2013: Chervenkova, Ludmila. Panevritmia zdrave i blagopoluchie. Edin bulgarski model za dvigatelna aktivnost. Sofia: UI „Kliment Ohridski“. ISBN 978-954-07-3575-7. Sofia.Dunov 1938: Dunov, Peter. Posoka na rastene. MOK (1932 – 1933) I Tom.Dunov 1949: Dunov, Peter. Velikata mudrost. MOK (1932 – 1933) I Tom.Dunov 1949: Dunov, Peter. Syrazmernost v prirodata. MOK (1932-1933) II Tom.Dunov 1993: Dunov, Peter. Panevritmia. Sofia.Dunov 2000: Dunov, Peter. Okultni upravneniq. Sbornik s izvadki ot lekcii. Sofia.Dunov 2010: Dunov, Peter. Absolutnata spravedlivost. OKK, 4 god. (1924 – 1925).Jonov 2003: Jonov, Jonko. Panevritmiata kato sistema za harmonichno razvitie na choveka i obshtestvoto: Vtora nauchna konferencia po Panevritmia. Sdruzhenie Panevritmia, ISBN – 954-90922-3-2. Sofia, 2003, 13-15.Kajkov, Qnkova 2007: Kajkov, Dimitar, Antoaneta Qnkova, Zdrave chrez dvijenie sred prirodata: Treta nauchna konferencia po Panevritmia. Institut za izsledvane i prilagane na Panevritmiyata, ISBN-10: 954-90922-5-9. ISBN-13: 978-954-90922-5-7. Sofia, 2007, 8-17.Lambova, Ilieva 2007: Lambova, Krasimira, Dimitrina. Ilieva. Panevritmiata – vyzmojnosti za harmonichno razvitie na hora s naprednala vyzrast: Treta nauchna konferencia po Panevritmia. Institut za izsledvane i prilagane na Panevritmiyata, ISBN-10: 954-90922-5-9. ISBN-13: 978-954-90922-5-7. Sofia, 2007, 109-118.Qnkova 2001: Qnkova, Antoaneta. Panevritmiata kato sistema za harmonichno razvitie na choveka i obshtestvoto: Pyrva nauchna konferencia po Panevritmia. Sofia: NSA PRES. Sofia, 2001, 17-23.Qnkova 2007: Qnkova, Antoaneta. Panevritmiata kato sistema za harmonichno razvitie na choveka i obshtestvoto: Treta nauchna konferencia po Panevtitmia. Institut za izsledvane i prilagane na Panevritmiyata, ISBN-10: 954-90922-5-9. ISBN-13: 978-954-90922-5-7. Sofia, 2007, 56-59.Tilev, Koleva, Milcheva 2007: Tilev, Tilio, Koleva, Ivanka, Nadka Milcheva. Optimizirane na syrdecho-sydovata dejnost chrez Panevritmiata: Treta nauchna konferencia po Panevtitmia. Institut za izsledvane i prilagane na Panevritmiyata, ISBN-10: 954-90922-5-9. ISBN-13: 978-954-90922-5-7. Sofia, 2007, 114-118.Antonelli, Barbieri & Donelli 2019: Antonelli, Michelle, Barbieri, Grazia, Donelli Davide. Effects offorest bathing (shinrin-yoku) on levels of cortisol as a stress biomarker: a systematic review and meta analysis. Int J Biometeorol. 2019 Aug; 63(8):1117-1134. doi: 10.1007/s00484-019-01717-x. Epub 2019 Apr 18. PMID: 31001682.Farrow, Washburn 2019: Farrow Marc R., Washburn, Kyle. A Review of Field Experiments on the Effect of Forest Bathing on Anxiety and Heart Rate Variability. Glob Adv Health Med. 2019 May 16;8:2164956119848654. doi: 10.1177/2164956119848654. PMID: 31192052; PMCID: PMC6540467.Hansen, Jones, Tocchini 2017: Hansen, Margaret, Mary, Reo Jones, Kirsten Tocchini. Shinrin-Yoku (Forest Bathing) and Nature Therapy: A State-of-the-Art Review. 2017 Jul 28;14(8):851. doi: 10.3390/ijerph14080851. PMID: 28788101; PMCID: PMC5580555; DOI: 10.3390/ijerph14080851Hansen, Jones 2020: Hansen, Margaret Mary, Jones, Reo. The Interrelationship of Shinrin-Yoku and Spirituality: A Scoping Review. 2020 Dec;26(12):1093-1104. doi: 10.1089/acm.2020.0193. Epub 2020 Sep 15.Ideno et al. 2017: Ideno Yuki, Hayashi Kunihiko, Abe Yukina, Ueda Kayo, Iso Hiroyasu, Noda Mitsuhiko, Lee Jung-Su, Suzuki Shosuke. Blood pressure-lowering effect of Shinrin-yoku (Forest bathing): a systematic review and meta-analysis. BMC Complement Altern Med. 2017Aug 16;17(1):409. doi: 10.1186/s12906-017-1912-z. PMID: 28814305; PMCID: PMC5559777.Li 2019: Li, Qing. Effect of forest bathing (shinrin-yoku) on human health: A review of the literature. 2019 May 13; S1 (HS):135-143. doi: 10.3917/spub.190.0135.Li 2022: Li, Qing. Effects of forest environment (Shinrin-yoku/Forest bathing) on health promotion and disease prevention -the Establishment of ‘Forest Medicine’. PMID: 36328581 PMCID: PMC9665958 DOI: 10.1265/ehpm.22-00160Li et al. 2022: Li Qing, Ochiai H, Ochiai T, Takayama N, Kumeda S, Miura T, Aoyagi Y, Imai M. Effects of forest bathing (shinrin-yoku) on serotonin in serum, depressive symptoms and subjective sleep quality in middle-aged males. Environ Health Prev Med. 2022;27:44. doi: 10.1265/ehpm.22-00136. PMID: 36328588; PMCID: PMC9665960.Morita et al. 2006: Morita Emi, Fukuda S, Nagano J, Hamajima N, Yamamoto H, Iwai Y, Nakashima T, Ohira H, Shirakawa T. Psychological effects offorest environments on healthy adults: Shinrin-yoku (forest-air bathing, walking) as a possible method of stress reduction. Public Health. 2007 Jan;121(1):54-63. doi: 10.1016/j.puhe.2006.05.024. Epub 2006 Oct 20. PMID: 17055544.Morita et al. 2024: Morita Emi, Kadotani H, Yamada N, Sasakabe T, Kawai S, Naito M, Tamura T, Wakai K. The Inverse Association between the Frequency of Forest Walking (Shinrin-yoku) and the Prevalence of Insomnia Symptoms in the General Japanese Population: A Japan Multi-Institutional Collaborative Cohort Daiko Study. Int J Environ Res Public Health. 2024 Mar 15;21(3):350. doi: 10.3390/ijerph21030350. PMID: 38541349; PMCID: PMC10970638.Ohtsuka et al. 1998: Ohtsuka Y, Yabunaka N, Takayama S. Shinrin-yoku (forest-air bathing and walking) effectively decreases blood glucose levels in diabetic patients. Int J Biometeorol. 1998 Feb;41(3):125-7. doi: 10.1007/s004840050064. PMID: 9531856.Park et al. 2010: Park Bum Jin, Tsunetsugu Yuko, Kasetani Tamami, Kagawa Takahide, Miyazaki Yoshfumi. The physiological effects of Shinrin-yoku (taking in the forest atmosphere or forest bathing): evidence from field experiments in 24 forests across Japan. Environ Health Prev Med. 2010 Jan;15(1):18-26. doi: 10.1007/s12199-009-0086-9. PMID: 19568835; PMCID: PMC2793346.Pasieka 2021: Pasieka, Janice L. Shinrin-yoku, yoga and other strategies in the fight against COVID-19. Surgery. 2022 Jan;171(1):94-95. doi: 10.1016/j.surg.2021.07.044. Epub 2021 Aug 31. PMID: 34548159; PMCID: PMC8405594.Piva et al. 2022: Piva Giovanni, Caruso Lorenzo, Gуmez Alberto Cruz, Calzolari Marta, Visintin Emilio Paolo, Davoli Pietromaria, Manfredini Fabio, Storari Alda, Spinozzi Paola, Lamberti Nicola. Effects of forest walking on physical and mental health in elderly populations: a systematic review. Rev Environ Health. 2022 Oct 17;39(1):121-136. doi: 10.1515/reveh-2022-0093. PMID: 36239186.Song et al. 2019: Song Chorong., Ikei Harumi, Kagawa Takahide, Miyazaki Yoshifumi. Effects of Walking in a Forest on Young Women. Int J Environ Res Public Health. 2019 Jan 15;16(2):229. doi: 10.3390/ijerph16020229. PMID: 30650572; PMCID: PMC6351942.Vermeesch et al. 2024: Vermeesch Amber L, Ellsworth-Kopkowski Alexis, Prather Jenifer G, Passel Cheryl, Rogers Heidi Honegger, Hansen Margaret M. Shinrin-Yoku (Forest Bathing): A Scoping Review of the Global Research on the Effects of Spending Time in Nature. Glob Adv Integr Med Health. 2024 Feb 27;13:27536130241231258. doi: 10.1177/27536130241231258. PMID: 38420597; PMCID: PMC10901062.WHO 2010: Clobal recommendation on Physical Activity for Health, WHO Library Gataloguing-Publiation Data.Yamaguchi et al. 2006: Yamaguchi M, Deguchi M, Miyazaki Y. The effects of exercise in forest and urban environments on sympathetic nervous activity of normal young adults. J Int Med Res. 2006 Mar-Apr;34(2):152-9. doi: 10.1177/147323000603400204. PMID: 16749410.Yau & Loke 2020: Yau Ka-Yin Katherine, Loke Ailice Y. Effects of forest bathing on pre hypertensive and hypertensive adults: a review of the literature. Environ Health Prev Med. 2020 Jun 22;25(1):23. doi: 10.1186/s12199-020-00856-7. PMID: 32571202; PMCID: PMC7310560.
Keywords: Shinrin-yoku; Forest Medicine